Alignment of Assessment Tasks with the Intended Learning Outcomes in “EPP” and “EMS” courses of ELESP UNJ: A Content Analysis - Akbar, Intan Miutiara; Sulastini, Sri (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2022)
This study aims at investigating the extent to which assessment tasks (ATs) and intended learning outcomes (ILOs) in Phonetics & Phonology (EPP) and English Morphology & Syntax (EMS) courses of ELESP are well aligned, and how their alignment with the knowledge (KD) and cognitive process dimension (CPD) is. Deductive qualitative content analysis techniques were implemented on the RPS document and assessment tools. It was found that 83% of the ATs in the EPP course are well-aligned with the ILOs. They support the students’ ability to Remember (8,82%), Understand (20,59%), and Apply (41,18%) the Conceptual (82,35%) and Procedural (17,65%) knowledge, while Analyze and Evaluate cover 2,94% and 26,47% respectively. However, the ATs tested students’ ability to Understand (25%) and Apply (75%) Conceptual (95%), and Metacognitive (5%) knowledge resulting in a misaligned teaching and learning exercise. In the EMS course, three out of six items (50%) of ATs are partially aligned, while only one AT (17%) is well-aligned with the ILOs. The ILOs support the students’ ability to Understand (50%) Conceptual (66,67%) and Metacognitive (33,33%) knowledge while the Analysis covers 50%. However, the ATs tested students’ ability to Understand (66,67%) and Apply (33,33%) Conceptual (100%) knowledge was misaligned.